2012
DOI: 10.1593/neo.111444
|View full text |Cite
|
Sign up to set email alerts
|

IκB Kinases Modulate the Activity of the Androgen Receptor in Prostate Carcinoma Cell Lines

Abstract: Enhanced nuclear localization of nuclear factor κB (NF-κB) in prostate cancer (PCa) samples and constitutive NF-κB signaling in a class of PCa cell lines with low androgen receptor (AR) expression (PC3 and DU-145) imply an important role of the IκB kinase (IKK)/NF-κB system in PCa. However, most PCa and PCa cell lines depend on the activity of the AR, and the role of NF-κB in these AR-expressing PCa remains unclear. Here, we demonstrate that inhibition of NF-κB signaling by the IKK inhibitor BMS345541 reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…IKK and IKK2 have recently been shown to phosphorylate the AR in vitro, consistent with the IKK inhibitor BMS345541 being able to reduce AR-P in vivo (Jain et al 2012), indicating crosstalk with yet another pathway and further demonstrating the increasing complexity of AR signalling.…”
Section: Ar-p Under Androgen-depleted Conditionssupporting
confidence: 55%
“…IKK and IKK2 have recently been shown to phosphorylate the AR in vitro, consistent with the IKK inhibitor BMS345541 being able to reduce AR-P in vivo (Jain et al 2012), indicating crosstalk with yet another pathway and further demonstrating the increasing complexity of AR signalling.…”
Section: Ar-p Under Androgen-depleted Conditionssupporting
confidence: 55%
“…While no activated IKKα was detected in nuclear fractions of normal human prostate or benign prostate hyperplasia, stage 4 tumors exhibited the highest nuclear levels and activity of IKKα (64). Furthermore, a recent study showed that IKKα regulates expression of androgen receptor in prostate cancer cells (65). …”
Section: Discussionmentioning
confidence: 99%
“…Another IKK‐inhibitor, BMS345541, was shown to reduce proliferation in AR‐expressing PCa cell lines. This effect was accompanied by a reduction in AR activity . To date, however, none of these agents has received clinical approval and further development is warranted.…”
Section: Targeting the Nf‐κb Pathwaymentioning
confidence: 99%